Closed loop oscillating heat pipe as heating device for copper plate - Kamonpet P. (2017)
© Published under licence by IOP Publishing Ltd. In manufacturing parts by molding method, temperature uniformity of the mold holds a very crucial aspect for the quality of the parts. Studies have been carried out in searching for effective method in controlling the mold temperature. Using of heat pipe is one of the many effective ways to control the temperature of the molding area to the right uniform level. Recently, there has been the development of oscillating heat pipe and its application is very promising. The semi-empirical correlation for closed-loop oscillating heat pipe (CLOHP) with the STD of ±30% was used in design of CLOHP in this study. By placing CLOHP in the copper plate at some distance from the plate surface and allow CLOHP to heat the plate up to the set surface temperature, the temperature of the plate was recorded. It is found that CLOHP can be effectively used as a heat source to transfer heat to copper plate with excellent temperature distribution. The STDs of heat rate of all experiments are well in the range of ±30% of the correlation used.